Primary care providers' experiences with urine toxicology tests to manage prescription opioid misuse and substance use among chronic noncancer pain patients in safety net health care settings. Issue 1 (2nd January 2016) - Ceasar, Rachel; Chang, Jamie; Zamora, Kara; Hurstak, Emily; Kushel, Margot; Miaskowski, Christine; Knight, Kelly
ABSTRACT: Background: Guideline recommendations to reduce prescription opioid misuse among patients with chronic noncancer pain include the routine use of urine toxicology tests for high-risk patients. Yet little is known about how the implementation of urine toxicology tests among patients with co-occurring chronic noncancer pain and substance use impacts primary care providers' management of misuse. Clinicians' perspectives on the benefits and challenges of implementing urine toxicology tests in the monitoring of opioid misuse and substance use in safety net health care settings are presented in this paper. Methods: Twenty-three primary care providers from 6 safety net health care settings whose patients had a diagnosis of co-occurring chronic noncancer pain and substance use were interviewed. Interviews were transcribed, coded, and analyzed using grounded theory methodology. Results: The benefits of implementing urine toxicology tests for primary care providers included less reliance on intuition to assess for misuse and the ability to identify unknown opioid misuse and/or substance use. The challenges of implementing urine toxicology tests included insufficient education and training about how to interpret and implement tests, and a lack of clarity on how and when to act on tests that indicated misuse and/or substance use. Conclusions: These data suggest that primary care clinicians' lack of education and training to interpret and implement urine toxicology tests may impact their management of patient opioid misuse and/or substance use. Clinicians may benefit from additional education and training about the clinical implementation and use of urine toxicology tests. Additional research is needed on how primary care providers implementation and use of urine toxicology tests impacts chronic noncancer pain management in primary care and safety net health care settings among patients with co-occurring chronic non cancer pain and substance use.